PENGARUH PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING - Daniswara, Fajar Nizar; Gultom, Henry Casandra; Akbar, Shofif Sobaruddin (Gapenas Publisher, 2025)
This study aims to analyze the influence of price perception and promotion on purchasing decisions, with purchase intention as an intervening variable among Demakshoes consumers in Demak Regency. Demakshoes experiences instability and declining sales in certain months. This study used a quantitative approach with data collection techniques through distributing questionnaires to 96 respondents, who are Demakshoes consumers. Data analysis was conducted using the Structural Equation Modeling (SEM) method with the assistance of SmartPLS software. The results show that price perception and promotion significantly influence purchase intention. Price perception significantly influences purchase decisions. Promotion does not influence purchase decisions. Purchase intention significantly influences purchase decisions. Price perception and promotion influence purchase decisions through purchase intention as an intervening variable